Effects of Polyhalite Fertilization on Skin Quality of Potato Tuber - Keren-Keiserman, Alexandra; Baghel, Ravi Singh; Fogelman, Edna; Faingold, Inna; Zig, Uri; Yermiyahu, Uri; Ginzberg, Idit (Frontiers in Plant Science, 2019)
The protective peel of potato tuber consists of periderm tissue, the outmost cell layers of which contain corky cell walls and are termed 'skin'. The skin protects the tuber from water loss and pathogen invasion, and its visual appearance is a highly important marketing factor. Physiological skin blemishes are of great concern, mainly russeting disorder and skinning injuries. We previously showed that application of calcium (Ca) reduces the rate and severity of skin russeting. Here, polyhalite fertilization was tested as an alternative source of Ca. The polyhalite mineral is a hydrated sulfate of potassium (K), Ca and magnesium (Mg), and thus contains additional important nutrients that may contribute to skin quality. Furthermore, in view of the direct interaction of soil mineral elements with the tuber skin, we tested application of polyhalite at the end of the growth period, assuming that providing the mineral at the last stages of skin development may enhance its quality. Accordingly, polyhalite was applied at three time points: pre-planting, in-season at around 3–4 weeks prior to haulm desiccation, and 2 days post-haulm desiccation. The experiments included several cultivars and locations. Data indicated that late application of polyhalite, after haulm desiccation, results in reduced concentrations of Ca and Mg and increased concentration of K in the tuber peel of fertilized plants compared to controls. Tuber appearance was improved, and the expression of FHT and CYP86A33, indicator genes for skin suberization, was significantly upregulated. Earlier applications of the polyhalite mineral did not alter mineral elements concentrations in the tuber peel compared to control plants. Overall, polyhalite fertilization positively affected tuber skin appearance and skin-related gene expression. However, the effect was moderate, and the mineral did not fully mitigate skin imperfections. The effect of polyhalite may be dependent on local conditions and cultivar type.